Kinerja Guru Pendidikan Agama Islam di SMK Negeri 1 Koto Balingka Kabupaten Pasaman Barat - Ridha Aulia Nst; Wedra Aprison; Salmi Wati; Arifmiboy Arifmiboy (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
PAI teachers at SMK Negeri 1 Koto Balingka, West Pasaman Regency have performance that is not yet included in the good criteria, meaning that the teachers in educating their students are not yet professional. In implementing learning, PAI teachers still use conventional teaching methods without paying attention to the learning implementation plan, namely the mismatch between learning implementation and the learning implementation plan that has been made by the teacher in the learning process. The research approach used in this research is a quantitative descriptive approach. The population in this research were students, totaling 115 teachers. The sampling technique used was the Proportional Random Sampling technique, obtaining 89 student samples. The data collection technique used was a questionnaire using a Likert scale as the main technique. The data analysis technique uses a percentage formula. Test the validity of the instrument using the Product Moment formula, and test reliability using the Cronbach's Alpha formula. The results of the research show that the performance of Islamic Religious Education Teachers at SMK Negeri 1 Koto Balingka, West Pasaman Regency in the learning planning aspect is included in the high category with an interpretation value of 89.04. In the aspect of learning implementation it is included in the high category with an interpretation value of 82.99 and in the The learning evaluation aspect is included in the high category with an interpretation value of 87.64.